Alasdair MacIntyre, Charles Taylor, and the demise of naturalism : reunifying political theory and social science - Blakely, Jason, 1980- (University of Notre Dame Press, 2016)
Blakely argues that the resources for overcoming the divide between the empirical and the normative of society are available in the intellectual developments of Charles Taylor and Alasdair MacIntyre.